Empowerment through entrepreneurship: An intersectional analysis of race, gender, and class in Self Made - Wajiran, Wajiran; Widiyanti, Ana (Universitas Ahmad Dahlan, 2024)
The miniseries Self Made depicts Black women's empowerment, intersectionality, and entrepreneurship. The study examines how the series depicts Sarah Breedlove's socio-economic hardships as she overcomes racial, gender, and class oppression to become America's first self-made Black female millionaire through qualitative analysis of key scenes and dialogues. The study uses Black feminist theory and intersectionality to show how Sarah's entrepreneurial career empowers Black women by questioning beauty norms and providing economic opportunity. Analysis shows how the series criticizes racism and misogyny while glorifying resistance and communal cohesion. The analysis also highlights the series' relevance to racial and gender equality discourse in capitalist economies. The study shows how cultural representations like Self Made may drive social change and help us comprehend Black female entrepreneurs' particular obstacles by focusing on their intersectional experiences. This research advances media studies, feminist theory, and African American cultural history by demonstrating entrepreneurship's transformative capacity to empower.